ICRC Audiovisual Archives - Internationales Komitee vom Roten Kreuz (2021)
The ICRC’s collections of sound recordings, film footage, videos and photos illustrate and document the activities of the ICRC and of the International Red Cross and Red Crescent Movement as a whole from the end of the 19th century up to the present day, in all operational contexts. These archives have been continually expanded over more than 150 years and today represent a significant heritage in the field of humanitarian law and action. They preserve the memory of victims of armed conflicts and other situations of violence to which the ICRC has responded throughout its history." [self-description]